Rice production in West Africa : Analyzing the impacts of risks and constraints on yields and rice farmers' food security - (:unkn) unknown (My University, 2023)
Rice, with its rapidly growing importance as a staple food, plays a key role in West African diets, accounting for nearly 40% of the total volume of cereals consumed. In the context of the 2008 food price crisis, several West African countries have proclaimed their goal of rice self-sufficiency by 2050, through expansion of cultivation areas and intensification of rice farming. The objective of this thesis is to assess the production and market risks associated with increased rice production in West Africa and to evaluate their impact on the welfare and food security of rice producers.In a first study, the potential impact of reallocating resources such as land, labor or capital to rice production at the expense of other staple food crops such as cassava, maize, millet, sorghum or yam is examined. On average across the region, rice yields are more variable, by about 20%, than those of the other five staple food crops. Rice tends to have more variable yields than the other crops in areas where they are traditionally grown (i.e., tubers in the Guinean zone, and sorghum and millet in the Sahelian and Sudanian zones). Rice yields, across all cropping systems, tend to be more variable than those of other crops in areas where rainfall variability is greatest.The impact of agricultural practices and climate risk on rice yields is examined in a second study, via the construction of rice production functions for four representative cropping systems (i.e., rainfed lowland system, improved lowland system, irrigated system, rainfed upland system). The statistical study of yields shows that intensive practices (i.e., use of fertilizers, pesticides, improved varieties, improved water management) significantly increase average yields but do not lead to a stabilization of yields, at the scale of an administrative region 1. In the Guinean and Sudanian zones, where water scarcity and drought risks are lower, it is the frequency of weeding that has the greatest impact on
Keywords: African Research